My double-edged life - Krueger, Jim (Tomo, 2007)
When you're fighting two battles, you need a friend to watch your back. Hana must defend herself against bullies at school, then face otherworldly warriors at home! Fortunately, she learns she's not the only new ninja in town. Tomo, her grandfather's weird little pet, has some pretty amazing moves of his own. Together they form a powerful team. But can they keep the evil forces of Argon Falls from taking the Spirit Sword?